High-temperature-resistant and high-stable ion sieve, and preparation method and application thereof
Patent Information
- Application Number
- CN202211665025.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-23
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-12-23
AI Technical Summary
[0007]本发明的目的是为了克服现有技术存在的杂质离子去除材料耐高温以及高温稳定性有待进一步提高的缺陷,提供一种耐高温、高稳定的离子筛及其制备方法和应用
[0034]This invention, through in-depth research on ion sieves, reveals that ion sieves with specific compositions and structural requirements exhibit excellent high-temperature resistance and stability. Even after prolonged placement in a high-temperature salt bath, these ion sieves do not undergo significant phase transformations, maintain structural stability, and do not release large amounts of impurities that contaminate the salt bath, nor cause obvious defects such as granular defects on the surface of the strengthened glass product. The ion sieve of this invention can continuously and stably absorb impurity ions, such as lithium ions which have a significant adverse effect on glass strengthening, for 24 hours in a 480℃ salt bath, while ensuring that the surface quality of the strengthened glass product meets requirements. Conversely, if the structure of the ion sieve does not meet the specific structural requirements of this invention, it will undergo significant phase transformations after prolonged placement in a high-temperature salt bath, ultimately leading to a significant decrease in the ion sieve's absorption capacity and effect for impurity ions. Furthermore, after prolonged placement in a high-temperature salt bath, the ion sieve may even precipitate impurity ions and other impurities back into the salt bath, contaminating it and causing obvious defects such as granular defects on the surface of the strengthened glass product.
Smart Images

Figure CN118236969B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ion sieve technology, and particularly relates to the purification technology of salt baths for chemical strengthening of glass. Specifically, it relates to a high-temperature resistant and highly stable ion sieve, its preparation method, and its application. Background Technology
[0002] During the chemical strengthening process of glass, alkali metal ions with large ionic radii (such as K) in the salt bath + Na + ) to replace alkali metal ions with small ionic radii (such as Na) in glass + Li + Within a certain depth range, a "squeezing effect" occurs, forming a specific stress distribution that hinders the propagation of microcracks in the glass, thereby increasing the glass's strength. Simultaneously, alkali metal ions with small ionic radii continuously enter the salt bath from the glass, increasing the content of these ions in the salt bath. These increased alkali metal ions also act as impurities in the salt bath. When alkali metal ions with small ionic radii (such as Li) in the salt bath... + When the content of Li exceeds a certain limit, it will severely hinder normal chemical strengthening, leading to a decrease in the stress level and a significant drop in mechanical strength of the subsequently strengthened glass, resulting in the final product failing to meet usage requirements. Furthermore, the Li content in the salt bath... + The increase in content will severely weaken the lithium-sodium exchange rate during the chemical strengthening of lithium aluminum silicon glass, resulting in a rapid decrease in the increase in glass size after strengthening. This will make it impossible to meet the requirements for the glass size deviation range in mobile phone cover glass applications, ultimately leading to an increase in the dimensional defect rate of chemically strengthened glass.
[0003] In response to the above situation, the industry has proposed a solution of introducing impurity ion removal materials into the salt bath. These materials are used to remove excessive alkali metal ions with small ionic radii (such as Li) from the salt bath. + ), to remove alkali metal ions with small ionic radii (such as Li) from the salt bath. + Materials with content controlled within limits should be used to ensure the normal operation of the salt bath and to avoid the presence of alkali metal ions with small ionic radii (such as Li) in the salt bath. + Too much of this can negatively impact the performance and quality of tempered glass.
[0004] Commonly used impurity ion removal materials in glass processing plants include phosphates and ion sieves. The principle behind phosphate removal is that phosphate ions react with impurity ions to form precipitates. For example, adding powdered sodium phosphate to a salt bath causes phosphate ions to react with lithium ions to form lithium phosphate, which then precipitates, thus reducing the content of the impurity Li+. However, lithium phosphate causes the salt bath to become cloudy, requiring a long clarification period before it can be used. Furthermore, some lithium phosphate particles easily adhere to the surface of the tempered glass, causing defects. In other words, using phosphates as impurity ion removal materials has limited effectiveness in improving the salt bath. To ensure the performance and quality of the tempered glass, the salt bath still needs to be replaced frequently, which not only hinders production efficiency but also increases tempering costs. Simultaneously, excessive precipitated lithium phosphate at the bottom of the salt bath reduces the effective working area, increasing the difficulty of cleaning the tempering furnace.
[0005] In glass processing plants, to ensure mass production efficiency, it is desirable to continuously feed glass to be strengthened into the salt bath furnace and strengthen it to obtain chemically strengthened glass that meets requirements. Simultaneously, it is also desirable to shorten the glass strengthening time by increasing the salt bath temperature. To achieve this, a solution is needed to effectively control the impurity ion content in the salt bath. If the impurity ion removal material cannot be used for extended periods and requires frequent replacement, this not only interrupts the strengthening process and affects mass production efficiency but also increases the amount of impurity ion removal material used. Furthermore, the removal of the impurity ion removal material can easily carry away large amounts of molten salt, leading to increased strengthening costs. Therefore, an impurity ion removal material that can be used stably in a high-temperature salt bath for extended periods is needed to reduce molten salt usage, improve production efficiency, and lower production costs.
[0006] After discovering the shortcomings of using phosphates as impurity ion removal materials, the applicant of this invention developed an ion sieve material capable of adsorbing impurity ions in a salt bath. For example, the applicant's earlier patent application CN112645610A disclosed a boron-free, phosphorus-free, highly stable ion sieve and its application, solving the problems of insufficient absorption capacity and poor absorption rate of lithium ions in a high-temperature salt bath during the production of chemically strengthened glass covers, particularly targeting the absorption of poisoned lithium ions. The applicant found that after adding the ion sieve developed by the applicant, the content of impurity ions in the salt bath was indeed well controlled, and a series of problems associated with using phosphates were avoided. However, its high-temperature resistance and high-temperature stability need further improvement. Summary of the Invention
[0007] The purpose of this invention is to overcome the shortcomings of existing impurity ion removal materials, such as the need for further improvement in high-temperature resistance and high-temperature stability, and to provide a high-temperature resistant, highly stable ion sieve, its preparation method, and applications. This ion sieve exhibits excellent high-temperature resistance and can be used stably for extended periods in high-temperature salt baths. It demonstrates excellent high-temperature stability, such as being able to continuously absorb impurity lithium ions for 24 hours in a 480℃ salt bath without frequent replacement, thus improving the production efficiency and reducing the production cost of chemically strengthened glass. Furthermore, it has a wide range of applications.
[0008] The inventors of this invention, through extensive research, discovered that the reason why the high-temperature resistance and high-temperature stability of existing impurity ion removal materials are difficult to further improve is that ordinary silicon-based ion sieves undergo significant crystal transformation after long-term use in high-temperature salt baths. Ion sieve materials that have undergone crystal transformation experience a decrease in lithium-ion absorption efficiency and may even release lithium ions back into the salt bath. Furthermore, ion sieve materials that have undergone crystal transformation release a large amount of impurities into the salt bath, contaminating it and affecting the quality of the strengthened glass, resulting in granular defects on the surface of the finished strengthened glass. Based on this, the inventors further researched and proposed this invention. This invention solves the problem that silicon-based ion sieves, due to crystal transformation during chemical strengthening processes, cannot stably absorb lithium ions for extended periods and release a large amount of impurities, thus affecting salt bath life and high-temperature stability.
[0009] To achieve the above objectives, in a first aspect, the present invention provides a high-temperature resistant and highly stable ion sieve.
[0010] In this invention, the composition of the ion sieve, based on the molar percentage of each oxide in the ion sieve, includes: SiO2: 46-60 mol%, Al2O3: 3-16 mol%, Y2O3: 0-3 mol%, R2O: 33-45 mol%; wherein, R2O is an alkali metal oxide.
[0011] The ion sieve satisfies: Not less than 1; among which, For the 830-1230 cm⁻¹ of the ion sieve Raman spectrum -1 After Gaussian deconvolution fitting of the spectral bands within the range, Q 3 The corresponding area, Q 3 Si-O in a silicon-oxygen tetrahedron with only one non-bridging oxygen atom - Stretching vibration peak; For the 830-1230 cm⁻¹ of the ion sieve Raman spectrum -1 After Gaussian deconvolution fitting of the spectral bands within the range, Q 2 The corresponding area, Q 2 Si-O in a silicon-oxygen tetrahedron with only two non-bridging oxygen atoms- Stretching vibration peak.
[0012] In some preferred embodiments, after the ion sieve is placed in a 480°C salt bath for 24 hours, the crystal content in the ion sieve is less than 10 wt%.
[0013] In some preferred embodiments,
[0014] In some preferred embodiments, the composition of the ion sieve satisfies the following: based on the molar percentage of each oxide in the ion sieve, 52.0 ≥ 0.85 × SiO2 + 0.15 × Al2O3 + 1.65 × Y2O3 ≥ 45.3.
[0015] More preferably, the composition of the ion sieve also satisfies the following: based on the molar percentage of each oxide in the ion sieve, 20.0 ≥ 0.50 × R2O ≥ 16.0; wherein R2O is Na2O and / or K2O, and more preferably, R2O is Na2O.
[0016] In some preferred embodiments, in the ion sieve,
[0017] The molar percentage of SiO2 is 49-60 mol%; and / or
[0018] The molar percentage of Al2O3 is 3-15 mol%; and / or
[0019] The molar percentage of Y₂O₃ is 1-3 mol%; and / or
[0020] The molar percentage of R2O is 33-40 mol%.
[0021] In some preferred embodiments, the composition of the ion sieve, based on the molar percentage of each oxide in the ion sieve, further includes: ZnO: 0-3 mol%, CaO: 0-3 mol%, MgO: 0-3 mol%, P2O5: 0-3 mol%, B2O3: 0-3 mol%; wherein the sum of the molar percentages of ZnO, CaO, MgO, P2O5, and B2O3 does not exceed 5 mol%.
[0022] More preferably, the ion sieve is substantially free of P2O5 and / or B2O3.
[0023] In some preferred embodiments, the ion sieve, with a mass ratio of 1 wt%, is added to a 480°C salt bath containing 105 ± 10 ppm of impurity lithium ions, based on the mass of the salt bath.
[0024] The variation curve of lithium ion concentration y in the salt bath with time x satisfies the following function: y=A1×exp(-x / b1)+A2×exp(-x / b2)+C0, wherein exp is an exponential function, 100>A1>30, 0<A2<31, 0<b1<5, 0<b2<25, 0<C0<50, and the unit of x is h.
[0025] In some preferred embodiments, the ion sieve is in granular, flake or porous shape, preferably granular, and the particle size of the granular ion sieve is preferably 1-10 mm.
[0026] In a second aspect, the present invention provides a method for preparing the ion sieve described in the first aspect, comprising the following steps: taking each raw material according to the formula, mixing them uniformly, then melting at 1300-1650°C to obtain a liquid material; then forming the material into granules, flakes or porous shapes.
[0027] In some preferred embodiments, the granular ion sieve is formed by water quenching, wherein the water quenching temperature is 10-80°C.
[0028] In a third aspect, the present invention provides a purification method for a salt bath for glass chemical strengthening, comprising the following step: introducing the ion sieve described in the first aspect into a salt bath to be purified at 350-550°C to perform an impurity ion adsorption reaction.
[0029] In some preferred embodiments, the dosage of the ion sieve is 0.5-5.0 wt% of the salt bath to be purified.
[0030] In some preferred embodiments, the duration of the adsorption reaction is 0.1-48.0 h.
[0031] In a fourth aspect, the present invention provides a method for preparing chemically strengthened glass, comprising: introducing the glass to be strengthened and the ion sieve described in the first aspect into an impurity ion-free salt bath for glass chemical strengthening, and performing chemical strengthening.
[0032] It should be understood that the preparation method herein realizes on-line purification of the ion sieve, and enables the ion sieve purification process to be performed simultaneously with the glass strengthening process, without suspending the strengthening process or frequently replacing the salt bath, which improves the production efficiency of chemically strengthened glass and reduces the production cost of chemically strengthened glass.
[0033] Beneficial effects:
[0034] This invention, through in-depth research on ion sieves, reveals that ion sieves with specific compositions and structural requirements exhibit excellent high-temperature resistance and stability. Even after prolonged placement in a high-temperature salt bath, these ion sieves do not undergo significant phase transformations, maintain structural stability, and do not release large amounts of impurities that contaminate the salt bath, nor cause obvious defects such as granular defects on the surface of the strengthened glass product. The ion sieve of this invention can continuously and stably absorb impurity ions, such as lithium ions which have a significant adverse effect on glass strengthening, for 24 hours in a 480℃ salt bath, while ensuring that the surface quality of the strengthened glass product meets requirements. Conversely, if the structure of the ion sieve does not meet the specific structural requirements of this invention, it will undergo significant phase transformations after prolonged placement in a high-temperature salt bath, ultimately leading to a significant decrease in the ion sieve's absorption capacity and effect for impurity ions. Furthermore, after prolonged placement in a high-temperature salt bath, the ion sieve may even precipitate impurity ions and other impurities back into the salt bath, contaminating it and causing obvious defects such as granular defects on the surface of the strengthened glass product. Attached Figure Description
[0035] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0036] Figure 1a The initial XRD patterns of the ion sieves in Examples 1-4;
[0037] Figure 1b The initial XRD patterns of the ion sieves in Comparative Examples 1-4 are shown.
[0038] Figure 2a The XRD patterns of the ion sieves in Examples 1-4 after absorbing lithium ions in a 480°C salt bath for 24 hours are shown.
[0039] Figure 2b The XRD patterns of the ion sieves of Comparative Examples 1-4 after absorbing lithium ions in a salt bath at 480℃ for 24 hours are shown.
[0040] Figure 3a The graph shows the trend of lithium ion concentration over time in a 480°C salt bath for the ion sieves of Examples 1-4.
[0041] Figure 3b The graph shows the trend of lithium ion concentration over time in a 480℃ salt bath for the ion sieves used in Comparative Examples 1-4.
[0042] Figure 4The graph shows the fitting results of the lithium ion concentration change over time in Example 1.
[0043] Figure 5 The graph shows the fitting results of the lithium ion concentration change over time in Example 2.
[0044] Figure 6 The graph shows the fitting results of the lithium ion concentration change over time in Example 3.
[0045] Figure 7 The graph shows the fitting results of the lithium ion concentration change over time in Example 4.
[0046] Figure 8 The image shows the surface of the reinforced glass product obtained after the ion sieve of Example 1 directly participates in the chemical strengthening process.
[0047] Figure 9 The image shows the surface of the reinforced glass product obtained after the ion sieve of Comparative Example 1 directly participates in the chemical strengthening process.
[0048] Figure 10 The image shows the surface of the finished reinforced glass obtained after the ion sieve of Comparative Example 2 directly participates in the chemical strengthening process. Detailed Implementation
[0049] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the ranges, the endpoint values of the ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. The terms "optional" and "discretionary" mean that they may or may not be included (or may or may not be present).
[0050] The corresponding test methods involved in this invention are as follows:
[0051] 1. Ion sieve Raman spectroscopy test
[0052] The ion sieve was ground into a fine powder with a particle size of less than 75 μm, and then tested with a laser Raman spectrometer to obtain the Raman spectrum.
[0053] The test conditions were: wavenumber range of 100-1500 cm⁻¹ -1 Spectral resolution of 1-2 cm -1 .
[0054] The laser Raman spectrometer used in this invention is an INVIA model manufactured by RENISHAW, a British company.
[0055] 2. XRD pattern testing of ion sieves
[0056] (1) XRD pattern test of the initial ion sieve
[0057] The initial ion sieve that did not participate in the salt bath purification was ground into fine powder with a particle size of less than 75 μm. Then, it was tested with an X-ray diffractometer to obtain the XRD diffraction peak curve, i.e., the XRD spectrum.
[0058] The test conditions were as follows: incident angle range of 2θ = 10°-80°, scanning speed of 6° / min, operating voltage of 40kV, and operating current of 30mA.
[0059] (2) XRD pattern testing of ion sieves after salt bath purification
[0060] The initial ion sieve was placed in a 480°C test salt bath containing less than 1000 ppm of impurity lithium ions for 24 hours for purification, and then removed. The removed ion sieve was ground into a fine powder with a particle size of less than 75 μm, and then tested using an X-ray diffractometer to obtain the XRD diffraction peak curve, i.e., the XRD spectrum. The test salt bath used in this invention is a sodium nitrate salt bath containing 105 ± 10 ppm of impurity lithium ions.
[0061] The test conditions were as follows: incident angle range of 2θ = 10°-80°, scanning speed of 6° / min, operating voltage of 40kV, and operating current of 30mA.
[0062] The X-ray diffractometer used in this invention is the Shimadzu XRD_6100.
[0063] 3. Crystal content test in ion sieves
[0064] The crystal content in an ion sieve is measured by the proportion of the crystal phase peak area in the XRD pattern of the ion sieve after salt bath purification. In other words, the ratio of the crystal phase peak area fitted based on the XRD pattern to the total fitted peak area is the crystal content.
[0065] In this invention, an X-ray diffractometer is used to test the ion sieve after salt bath purification, and the X-ray diffractometer test result file (RAW format) is imported into the X-ray diffraction data refinement software (such as Jade, Gsas, Fullprof, Maud) for fitting and calculation.
[0066] 4. Lithium ion concentration (or content) test in salt bath
[0067] After the ion sieve was added to the salt bath to be purified, the concentration of lithium ions in the salt bath at different times was detected using an atomic absorption spectrophotometer, with time as the variable.
[0068] In a first aspect, the present invention provides a high-temperature resistant and highly stable ion sieve, wherein the composition of the ion sieve, based on the molar percentage of each oxide in the ion sieve, comprises: SiO2: 46-60 mol%, Al2O3: 3-16 mol%, Y2O3: 0-3 mol%, R2O: 33-45 mol%; wherein R2O is an alkali metal oxide; the ion sieve satisfies: Not less than 1; among which, For the 830-1230 cm⁻¹ of the ion sieve Raman spectrum -1 After Gaussian deconvolution fitting of the spectral bands within the range, Q 3 The corresponding area, Q 3 Si-O in a silicon-oxygen tetrahedron with only one non-bridging oxygen atom - Stretching vibration peak; For the 830-1230 cm⁻¹ of the ion sieve Raman spectrum -1 After Gaussian deconvolution fitting of the spectral bands within the range, Q 2 The corresponding area, Q 2 Si-O in a silicon-oxygen tetrahedron with only two non-bridging oxygen atoms - Stretching vibration peak. This is understandable. Area units and same.
[0069] The working principle of each component oxide is as follows:
[0070] SiO2 is used to form covalent bonds, constituting the framework of the ion sieve network structure. The choice of its composition and content directly affects the adsorption performance of the ion sieve network structure and the thermal stability of the ion sieve in high-temperature environments. Too low a SiO2 content leads to poor formability of the ion sieve, while excessive SiO2 results in high viscosity of the composition, causing melting difficulties. Therefore, in this invention, the molar percentage of SiO2 is 46-60 mol%. In some embodiments, the SiO2 content can be 46 mol%, 47 mol%, 48 mol%, 49 mol%, 50 mol%, 51 mol%, 52 mol%, 53 mol%, 54 mol%, 55 mol%, 56 mol%, 57 mol%, 58 mol%, 59 mol%, 60 mol%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0071] Al2O3 is a component of the network architecture and is beneficial for enhancing the absorption rate of impurity ions during the adsorption process of the ion sieve and improving the ion sieve's resistance to decomposition at high temperatures. However, excessive alumina content can lead to difficulties in ion sieve molding. Therefore, in this invention, the molar percentage of Al2O3 is 3-16 mol%. In some embodiments, the Al2O3 content can be 3 mol%, 4 mol%, 5 mol%, 6 mol%, 7 mol%, 8 mol%, 9 mol%, 10 mol%, 11 mol%, 12 mol%, 13 mol%, 14 mol%, 15 mol%, 16 mol%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0072] An appropriate amount of Y₂O₃ can improve the hardness and chemical stability of ion sieves, but when the Y₂O₃ content is high, the tendency for ion sieve crystallization increases. Therefore, in this invention, the molar percentage of Y₂O₃ is 0-3 mol%. In some embodiments, the Y₂O₃ content can be 0, 0.5 mol%, 1 mol%, 1.5 mol%, 2 mol%, 2.5 mol%, 3 mol%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0073] Alkali metal oxides (R₂O) provide alkali metal ions for ion exchange, which helps ensure the ion sieve's ability to absorb impurity ions. However, they also provide free oxygen, affecting the structural stability of the ion sieve. In other words, the R₂O content directly affects the ion sieve's ability to adsorb impurity ions and its stability in a high-temperature salt bath. Therefore, in this invention, the molar percentage of R₂O is 33-45 mol%. In some embodiments, the R₂O content can be 33 mol%, 34 mol%, 35 mol%, 36 mol%, 37 mol%, 38 mol%, 39 mol%, 40 mol%, 41 mol%, 42 mol%, 43 mol%, 44 mol%, 45 mol%, etc., as well as all ranges and sub-ranges between these values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.
[0074] In some preferred embodiments, after the ion sieve is placed in a 480°C salt bath for 24 hours, the crystal content in the ion sieve is less than 10 wt%, wherein the crystal content is measured as the proportion of the crystal phase peak area in the XRD pattern of the ion sieve.
[0075] In this invention, the Gaussian deconvolution fitting refers to importing the laser Raman spectrometer test result file (.txt format) into Origin (such as Origin 2022 version) and selecting 830-1230 cm⁻¹. -1 By analyzing the spectral bands within the specified range and performing deconvolution fitting and calculation using the Gaussian function, Q can be obtained. 3 Q 2 The corresponding area, the fitted Q 3 Area and fitted Q 2 The ratio of areas is
[0076] In some preferred embodiments,
[0077] In some implementations... The values can be 1.00, 1.05, 1.30, 1.50, 2.00, 2.30, 2.50, 2.80, 3.00, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in the embodiments, any of the above ranges can be combined with any other range. Through research and verification, the inventors have discovered that the ion sieve provided by this invention, with a specific composition and meeting specific structural requirements, possesses excellent high-temperature resistance and high-temperature stability. Even after being placed in a high-temperature salt bath for a prolonged period, the ion sieve does not undergo significant crystal phase transformation, demonstrating structural stability.
[0078] In some preferred embodiments, the composition of the ion sieve satisfies the following condition: 52.0 ≥ 0.85 × SiO2 + 0.15 × Al2O3 + 1.65 × Y2O3 ≥ 45.3, based on the molar percentage of each oxide in the ion sieve. Under this preferred embodiment, the inventors of this invention, through extensive research, discovered that the influence of each key component oxide on high-temperature stability varies, and that the above conditions can be met. Ion sieves with a specific structure of not less than 1 can significantly improve the structural stability of ion sieves, and at the same time facilitate the melting and forming of ion sieves.
[0079] In some implementations, the value of 0.85×SiO2+0.15×Al2O3+1.65×Y2O3 can be 45.3, 46.0, 47.0, 48.0, 49.0, 50.0, 51.0, 51.5, 52.0, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in implementations, any of the above ranges can be combined with any other range.
[0080] In the above preferred embodiment, Y2O3 may or may not be contained. When Y2O3 is contained, the effect of Y2O3 on the structural stability of the ion sieve is much greater than that of SiO2 and Al2O3. Controlling the content of Y2O3 under the above conditions is more conducive to improving high-temperature stability.
[0081] In this invention, while satisfying the condition of 52.0≥0.85×SiO2+0.15×Al2O3+1.65×Y2O3≥45.3, the ion sieve may also contain other components.
[0082] In some preferred embodiments, the composition of the ion sieve satisfies the following: based on the molar percentage of each oxide in the ion sieve, 20.0 ≥ 0.50 × R₂O ≥ 16.0, where R₂O is Na₂O and / or K₂O. Alkali metal oxides, on the one hand, can provide alkali metal ions to participate in ion exchange, which is beneficial for ensuring the ion sieve's absorption capacity for impurity ions; on the other hand, they can provide free oxygen, affecting the structural stability of the ion sieve. In this invention, 0.50 × R₂O is between 16.0 and 20.0, which can ensure the ion sieve's structural stability while achieving excellent adsorption capacity. It should be understood that during conventional glass chemical strengthening, the exchange mainly occurs between Na and Li ions contained in the glass and K and Na ions in the salt bath. The impurity ions present in the salt bath are mainly Li ions released from the glass into the salt bath. The fact that R₂O in the ion sieve is Na₂O and / or K₂O can better achieve the absorption and purification of impurity ions in the salt bath.
[0083] More preferably, R2O is Na2O. It should be understood that during chemical strengthening of glass, Na-Li exchange can result in a deeper compressive stress layer, which is more beneficial for improving the glass's impact resistance. To achieve this, Li ions in the glass are exchanged for Na ions in the salt bath and enter the salt bath as impurity ions. Simultaneously, the inventors discovered that an excessive concentration of impurity lithium ions in the salt bath has a highly detrimental effect on glass strengthening. Since all R2O in the ion sieve is Na2O, it can better achieve the absorption and purification of lithium ions in the salt bath.
[0084] More preferably, the molar percentage of SiO2 in the ion sieve is 49-60 mol%.
[0085] More preferably, the molar percentage of Al2O3 in the ion sieve is 3-15 mol%.
[0086] More preferably, the molar percentage of Y₂O₃ in the ion sieve is 1-3 mol%.
[0087] More preferably, the molar percentage of R2O in the ion sieve is 33-40 mol%.
[0088] The ion sieve of the present invention may further comprise other metal oxides. Further preferably, the composition of the ion sieve further comprises, based on the mole percentage of each oxide in the ion sieve: ZnO: 0-3 mol%, CaO: 0-3 mol%, MgO: 0-3 mol%, P₂O₅: 0-3 mol%, B₂O₃: 0-3 mol%.
[0089] More preferably, the sum of the mole percentages of ZnO + CaO + MgO + P₂O₅ + B₂O₃ does not exceed 5 mol%. Under this preferred solution, it is more conducive to the high-temperature stability of the ion sieve and reduces the precipitation amount of crystals; meanwhile, it is more conducive to avoiding the reduction of the absorption efficiency of the ion sieve.
[0090] In the present invention, P₂O₅ and B₂O₃ can be included in the components of the ion sieve. However, when the content of these components is excessive, the chemical durability of the ion sieve tends to deteriorate, and when it is used in a high-temperature salt bath, it is more likely to cause random erosion on the surfaces of glass and glass-ceramics. Therefore, in the ion sieve of the present invention, it is preferred to be substantially free of P₂O₅ and / or B₂O₃. Herein, "substantially free" means that P₂O₅ and / or B₂O₃ are not actively added or compounded into the ion sieve, but may exist in a very small amount as contaminants or impurities.
[0091] In some preferred embodiments, based on the mass of the salt bath, the ion sieve with a mass proportion of 1 wt% is added into a 480°C salt bath containing 105±10 ppm of impurity lithium ions;
[0092] The change curve of lithium ion concentration y in the salt bath versus time x satisfies the following function: y=A₁×exp(-x / b₁)+A₂×exp(-x / b₂)+C₀, where exp is an exponential function, 100>A₁>30, 0<A₂<31, 0<b₁<5, 0<b₂<25, 0<C₀<50, and the unit of x is h. This preferred solution shows that the ion sieve of the present invention can achieve long-term continuous and stable absorption of impurity lithium ions in a high-temperature salt bath, that is, the ion sieve of the present invention has excellent high-temperature stability and excellent impurity ion absorption capacity.
[0093] It can be understood that in the above function, a data relationship (mathematical model) is established from the given discrete data points of y and x, a series of tiny straight line segments are obtained to connect these interpolation points into a curve, so that a smooth curve can be formed. This curve can be represented by exp (exponential function), where A₁, A₂, b₁, b₂ and C₀ are all coefficients determined by the given discrete data points.
[0094] A person skilled in the art can select the shape and particle size of the ion sieve according to actual requirements.
[0095] In some preferred embodiments, the ion sieve is granular, flake-like, or porous, preferably granular, and more preferably the particle size of the granular ion sieve is 1-10 mm. In some embodiments, the particle size of the granular ion sieve can be 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, etc., as well as all ranges and sub-ranges between the above values. More preferably, the particle size of the granular ion sieve is 2-5 mm. It should be understood that, in embodiments, any of the above ranges can be combined with any other range. Here, "particle size of the ion sieve" refers to the maximum diameter of the ion sieve particles.
[0096] In a second aspect, the present invention provides a method for preparing the ion sieve described in the first aspect, comprising the following steps: taking each raw material according to the formula, mixing them evenly, melting them at 1300-1650℃ to obtain a liquid material; and then making it into granular, flake, or porous form.
[0097] In some preferred embodiments, the melting time is more than 1 hour to ensure that all raw materials are fully melted and mixed evenly.
[0098] This invention enables the formation of granular ion sieves through water quenching. Preferably, the water quenching temperature is 10-80°C. In some embodiments, the water quenching temperature can be 10°C, 15°C, 20°C, 22°C, 25°C, 30°C, 35°C, 45°C, 50°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range. The size of the ion sieve particles is controlled by controlling the temperature, so that the particle size of the ion sieve particles meets the requirement of 1-10 mm.
[0099] In some preferred embodiments, the ion sieve can be made into a sheet-like or porous shape as needed. Exemplarily, a sheet-like ion sieve can be formed by external force rolling or drawing. Preferably, the sheet-like ion sieve is irregularly shaped, with the shortest side controlled to be at least 0.3 cm, the maximum side less than 20 cm, and the thickness 0.3-1.0 mm. Exemplarily, a porous ion sieve can be formed by adding a foaming agent. Preferably, the porous ion sieve pores are fragmented, with a pore size of 1-10 mm. Preferably, the shortest side of the porous ion sieve block is at least 0.5 cm, and the maximum side less than 10 cm.
[0100] The ion sieve of the present invention can be used for purification in a salt bath containing impurity ions, or it can directly participate in the chemical enhancement process to adsorb / absorb lithium ions generated during the chemical enhancement process, and has a wide range of applications.
[0101] Thirdly, the present invention provides a purification method for a salt bath used in glass chemical strengthening, comprising the following steps: introducing the ion sieve described in the first aspect into the salt bath to be purified, and carrying out an impurity ion adsorption reaction. The temperature of the salt bath to be purified is preferably 350-550℃, which is more conducive to fully utilizing the adsorption / absorption performance of the ion sieve for lithium ions. The impurity ions adsorbed / absorbed by the ion sieve are mainly lithium ions.
[0102] It should be understood that "impurity ions" here refers to ions that were not actively introduced into the salt bath during initial salt bath preparation, such as lithium ions. "Adsorption reaction" here refers to alkali metal ions with large ionic radii in the ion sieve, such as K+. + Na + It will react with alkali metal ions with small ionic radii in the salt bath, such as Li + The ion exchange reaction is carried out to adsorb the alkali metal ions of impurities in the salt bath into the ion sieve, thereby purifying the salt bath.
[0103] In this invention, "salt bath purification" can be either online purification or purification of a salt bath after glass strengthening or a salt bath with excessive impurity ions. Online purification refers to directly introducing an ion sieve into an initial salt bath free of impurity ions. For example, the ion sieve can be placed in a carrier (such as a metal mesh) and then placed in the salt bath, allowing the ion sieve purification process (absorbing impurity ions from the salt bath) to occur simultaneously with the glass strengthening process. Purification of a salt bath after glass strengthening or a salt bath with excessive impurity ions refers to introducing an ion sieve into a salt bath containing impurity ions during or after the strengthening process for impurity ion adsorption.
[0104] In some preferred embodiments, the amount of the ion sieve used is 0.5-5.0 wt% of the salt bath to be purified. This invention enables effective purification of salt baths with a relatively low amount of ion sieve and exhibits excellent high-temperature resistance and stability.
[0105] The salt bath to be purified in this invention can be a pure potassium salt bath, a pure sodium salt bath, or a sodium-potassium mixed salt bath (i.e., a mixed salt bath containing lithium (impurity ions), sodium, and potassium) containing a large amount of lithium impurity ions. The salt bath is preferably a nitrate salt bath.
[0106] The lithium ion content in the salt bath to be purified described in this invention has a wide selectable range, and all can be purified using the ion sieve of this invention. For example, the impurity ion content in the salt bath to be purified can be 1-1000 ppm.
[0107] In some preferred embodiments, the reaction time is 0.1-48.0 h. The ion sieve of the present invention has excellent impurity ion absorption capacity, enabling efficient purification of impurity ion-containing salt baths in a short time. Simultaneously, the ion sieve of the present invention exhibits excellent high-temperature stability, maintaining a stable structure even in high-temperature salt baths and resisting significant crystal transformation. Therefore, this ion sieve can continuously and stably absorb impurity ions in a 480°C salt bath for 24 hours, enabling better online purification and avoiding frequent changes in salt baths or ion sieve materials. This is more conducive to improving the mass production efficiency of chemically strengthened glass and reducing costs.
[0108] Fourthly, this invention provides a method for preparing chemically strengthened glass, comprising: introducing the glass to be strengthened and the ion sieve described in the first aspect into a glass chemical strengthening salt bath free of impurity ions for chemical strengthening. It should be understood that this preparation method achieves online purification of the ion sieve, allowing the ion sieve purification process to be carried out simultaneously with the glass strengthening process, without needing to pause the strengthening process or frequently change the salt bath, thereby improving the production efficiency and reducing the production cost of chemically strengthened glass.
[0109] In this preparation method, during the chemical strengthening process, the ion sieve of the present invention can continuously and stably absorb the impurity ions generated during the ion exchange process in the salt bath, so that the impurity ions in the salt bath remain stable at a low level, ensuring the quality of the strengthened glass and avoiding the appearance of particulate defects on the surface of the strengthened glass product.
[0110] The salt bath free of impurity ions refers to a brand new salt bath that is essentially free of impurity ions, that is, an initial salt bath that has not yet been used for chemical strengthening of glass.
[0111] The present invention will be further described in detail below with reference to specific embodiments.
[0112] Example 1
[0113] An ion sieve, which The compositions of the oxides are shown in Table 1 below, where, For the 830-1230 cm⁻¹ of the ion sieve Raman spectrum -1 After Gaussian deconvolution fitting of the spectral bands within the range, Q 3 The corresponding area, Q 3 Si-O in a silicon-oxygen tetrahedron with only one non-bridging oxygen atom - Stretching vibration peak; For the 830-1230 cm⁻¹ of the ion sieve Raman spectrum -1 After Gaussian deconvolution fitting of the spectral bands within the range, Q 2 The corresponding area, Q 2Si-O in a silicon-oxygen tetrahedron with only two non-bridging oxygen atoms - Stretching vibration peak. The initial XRD pattern of the ion sieve, i.e., the XRD pattern of the initial ion sieve before salt bath purification, such as... Figure 1a As shown.
[0114] The preparation method is as follows: the raw materials of the ion sieve are prepared according to the formula in Table 1, and mixed evenly. Then, they are melted at 1500℃ for more than 1 hour to form a liquid state. The liquid state is formed by water quenching to form granular ion sieves with a particle size of 2-5mm. The water quenching temperature is 25℃.
[0115] Examples 2-4
[0116] The procedures were carried out according to Example 1, except that the formulation of the ion sieve was different, and the ion sieve contained... The difference is achieved by controlling the content of each oxide and the relationship between their contents, as shown in Table 1. The initial XRD pattern of the ion sieve, i.e., the XRD pattern of the initial ion sieve before salt bath purification, is shown below. Figure 1a As shown.
[0117] Comparative Examples 1-4
[0118] The procedures were carried out according to Example 1, except that the formulation of the ion sieve was different, and the ion sieve contained... The difference is achieved by controlling the content of each oxide and the relationship between their contents, as shown in Table 1. The initial XRD pattern of the ion sieve, i.e., the XRD pattern of the initial ion sieve before salt bath purification, is shown below. Figure 1b As shown.
[0119] Application Example 1
[0120] The ion sieves prepared in the above examples and comparative examples were placed in a test salt bath containing 105±10 ppm lithium ions at 480°C to carry out lithium ion adsorption reaction. The amount of ion sieve used was 1 wt% of the weight of the test salt bath.
[0121] The changes in lithium ion concentration y with time x in the above-mentioned test salt bath are shown in Table 2 below. Figure 3a , Figure 3b As shown in the figure, the results of fitting the variation curves of Examples 1-4 are as follows: Figure 4 , Figure 5 , Figure 6 , Figure 7 As shown.
[0122] After the ion sieve absorbed lithium ions in the test salt bath for 24 hours, the crystal content of the obtained ion sieve is shown in Table 1 below. The crystal content is measured as the proportion of the crystal phase peak area in the XRD spectrum of the ion sieve obtained after 24 hours of salt bath purification.
[0123] The XRD patterns of the ion sieves obtained after 24 h of salt bath purification are respectively shown in Figure 2a , Figure 2b .
[0124] Table 1
[0125]
[0126] Table 2
[0127]
[0128] It can be seen from Tables 1-2 that compared with the comparative examples, all the ion sieves of the examples of the present invention are formulations with a ratio greater than 1, which can continuously and stably adsorb lithium ions for 24 hours in a 480°C test salt bath, and after 24 hours of lithium ion adsorption, the crystal content in the ion sieves is all less than 10 wt%. It shows that the ion sieve adopting the solution of the embodiments of the present invention maintains a stable adsorption capacity for lithium ions in a high-temperature salt bath, and can maintain long-term stability in the high-temperature salt bath without crystal form change, will not cause pollution to the high-temperature salt bath due to long-term introduction of the ion sieve, and will not shorten the service life of the salt bath.
[0129] From Figure 1a , Figure 1b and Figure 2a , Figure 2b it can be seen that after the ion sieve of the embodiments of the present invention is continuously purified for 24 hours in a 480°C test salt bath, the crystal form of the ion sieve basically does not change, and the structure remains stable. However, after the ion sieve of the comparative example is continuously purified for 24 hours in a 480°C test salt bath, obvious crystal form transformation occurs, and a lot of crystals that are not contained in the initial ion sieve are produced. This shows that the ion sieve with specific composition and specific structure of the present invention has excellent high-temperature stability, and can be placed in a high-temperature salt bath for a long time to purify impurity ions.
[0130] From Figure 3a and Figure 3b and Figure 4-7 it can be seen that after placing the ion sieve of the embodiment in a 480°C test salt bath for lithium ion purification, the change of lithium ion concentration y in the salt bath with time x satisfies the following function: y=A1×exp(-x / b1)+A2×exp(-x / b2)+C0, wherein 100>A1>30, 0<A2<31, 0<b1<5, 0<b2<25, 0<C0<50, and exp is an exponential function. This shows that the ion sieve with specific composition and structure in the embodiments of the present invention can continuously and stably adsorb lithium ions for a long time in a high-temperature salt bath.
[0131] The ion sieves in the comparative examples did not satisfy the aforementioned function governing the change of lithium ion concentration over time in a 480℃ salt bath. For example, the corresponding fitting function for Comparative Example 2 was y = 29 × exp(-x / 1.52) - 10.92 × exp(x / 22.00) + 79.89. The ion sieves in Comparative Examples 1 and 4 even released lithium ions back into the salt bath after less than 10 hours of purification, causing an increase in the lithium ion concentration in the salt bath. This indicates that the ion sieves in the comparative examples, which do not satisfy the specific composition and structure of this invention, cannot stably adsorb lithium ions continuously for a long time in a high-temperature salt bath, and will release lithium ions into the salt bath later due to structural changes.
[0132] Application Example 2
[0133] Taking Example 1, Comparative Example 1, and Comparative Example 2 as examples, the ion sieve and the lithium aluminum silicon glass to be strengthened were simultaneously placed in a brand new 460°C sodium nitrate salt bath for continuous batch strengthening, with each batch strengthening time being 8 hours. After the strengthening of one batch of glass was completed, the strengthened glass and the ion sieve were removed from the salt bath together, and then a new batch of glass to be strengthened and a new ion sieve were added. The amount of ion sieve added to the salt bath each time was 1 wt% of the weight of the salt bath. When the strengthening reached the 8th batch, the images of the finished glass products obtained in Example 1 and Comparative Examples 1-2 are shown below. Figure 8 , Figure 9 and Figure 10 As shown.
[0134] Depend on Figure 8 It can be seen that when the ion sieve of Example 1 of this invention is used for salt bath purification, the surface of the strengthened glass is smooth and defect-free. However, when the ion sieve of Comparative Examples 1-2 is used for salt bath purification, obvious granular defects appear on the surface of the strengthened glass, such as... Figure 9-10 As shown within the dashed circle.
[0135] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A high-temperature resistant and highly stable ion sieve, characterized in that, In terms of mole percentages of respective oxides in the ion sieve, the composition of the ion sieve comprises: SiO₂: 46-60 mol%, Al₂O₃: 3-16 mol%, Y₂O₃: 0-3 mol%, R₂O: 33-45 mol%; wherein R₂O is an alkali metal oxide; The ion sieve satisfies: Not less than 1; among which, For the 830-1230 cm⁻¹ of the ion sieve Raman spectrum -1 After Gaussian deconvolution fitting of the spectral bands within the range, Q 3 The corresponding area, Q 3 Si-O in a silicon-oxygen tetrahedron with only one non-bridging oxygen atom - Stretching vibration peak; For the 830-1230 cm⁻¹ of the ion sieve Raman spectrum -1 After Gaussian deconvolution fitting of the spectral bands within the range, Q 2 The corresponding area, Q 2 Si-O in a silicon-oxygen tetrahedron with only two non-bridging oxygen atoms - Stretching vibration peak; The composition of the ion sieve satisfies: in terms of mole percentages of respective oxides in the ion sieve, 52.0≥0.85×SiO₂+0.15×Al₂O₃+1.65×Y₂O₃≥45.3; The composition of the ion sieve further satisfies: in terms of mole percentages of respective oxides in the ion sieve, 20.0≥0.50×R₂O≥16.0; wherein R₂O is Na₂O and / or K₂O.
2. The ion sieve according to claim 1, characterized in that, After placing the ion sieve in a 480°C salt bath for 24 hours, the crystal content in the ion sieve is less than 10 wt%.
3. The ion sieve according to claim 1, characterized in that, 3≥ ≥1。 4. The ion sieve according to claim 1, characterized in that, The composition of the ion sieve satisfies: in terms of mole percentages of respective oxides in the ion sieve, 51.5≥0.85×SiO₂+0.15×Al₂O₃+1.65×Y₂O₃≥46.
0.
5. The ion sieve according to claim 1, characterized in that, The composition of the ion sieve further satisfies: R₂O is Na₂O.
6. The ion sieve according to claim 1, characterized in that, In the ion sieve, the mole percentage of SiO₂ is 49-60 mol%; and / or the mole percentage of Al₂O₃ is 3-15 mol%; and / or the mole percentage of Y₂O₃ is 1-3 mol%; and / or the mole percentage of R₂O is 33-40 mol%.
7. The ion sieve according to claim 1, characterized in that, In terms of mole percentages of respective oxides in the ion sieve, the composition of the ion sieve further comprises: ZnO: 0-3 mol%, CaO: 0-3 mol%, MgO: 0-3 mol%, P₂O₅: 0-3 mol%, B₂O₃: 0-3 mol%; wherein the sum of mole percentages of ZnO+CaO+MgO+P₂O₅+B₂O₃ does not exceed 5 mol%.
8. The ion sieve according to claim 7, characterized in that, The ion sieve is substantially free of P₂O₅ and / or B₂O₃, wherein substantially free means that P₂O₅ and / or B₂O₃ are not actively added to the ion sieve, but allow for the presence of very small amounts as contaminants or impurities.
9. The ion sieve according to claim 1, characterized in that, Based on the mass of the salt bath, the ion sieve with a mass proportion of 1 wt% is added to a 480°C salt bath containing 105±10 ppm of impurity lithium ions; The change curve of lithium ion concentration y in the salt bath with time x satisfies the following function: y= A₁×exp(-x / b₁) + A₂×exp(-x / b₂)+C₀, where exp is an exponential function, and 100>A₁>30, 0<A₂<31, 0<b₁<5, 0<b₂<25, 0<C₀<50, and the unit of x is h.
10. The ion sieve according to claim 1, characterized in that, The ion sieve is granular, flaky or porous.
11. The ion sieve according to claim 10, characterized in that, The ion sieve is granular.
12. The ion sieve according to claim 11, characterized in that, The particle size of the granular ion sieve is 1 mm -10 mm.
13. The ion sieve according to claim 1, characterized in that, In terms of mole percentages of respective oxides in the ion sieve, the sum of the composition of the ion sieve satisfies 100%; In terms of mole percentages of respective oxides in the ion sieve, the composition of the ion sieve satisfies: the content of SiO₂ is 54 mol%; the content of Al₂O₃ is 7 mol%; R2O is Na2O, and the content of Na2O is 38 mol% The Y2O3 content is 1 mol% The value of 0.85×SiO2+0.15×Al2O3+1.65×Y2O3 is 48.6; R2O is Na2O, and the value of 0.50 × Na2O is 19.
14. The ion sieve according to claim 1, characterized in that, The sum of the components of the ion sieve, based on the molar percentage of each oxide in the ion sieve, satisfies 100%. Based on the molar percentage of each oxide in the ion sieve, the composition of the ion sieve satisfies: The SiO2 content is 60 mol% The Al2O3 content is 3 mol% R2O is Na2O, and the content of Na2O is 37 mol% The value of 0.85×SiO2+0.15×Al2O3+1.65×Y2O3 is 51.45; R2O is Na2O, and the value of 0.50 × Na2O is 18.
5.
15. The ion sieve according to claim 1, characterized in that, The sum of the components of the ion sieve, based on the molar percentage of each oxide in the ion sieve, satisfies 100%. Based on the molar percentage of each oxide in the ion sieve, the composition of the ion sieve satisfies: The SiO2 content is 49 mol% The Al2O3 content is 15 mol% The Y2O3 content is 1 mol% The CaO content is 2 mol% R2O is Na2O, and the content of Na2O is 33 mol% The value of 0.85×SiO2+0.15×Al2O3+1.65×Y2O3 is 45.55; R2O is Na2O, and the value of 0.50 × Na2O is 16.
5.
16. The ion sieve according to claim 1, characterized in that, The sum of the components of the ion sieve, based on the molar percentage of each oxide in the ion sieve, satisfies 100%. Based on the molar percentage of each oxide in the ion sieve, the composition of the ion sieve satisfies: The SiO2 content is 55 mol% The content of Al2O3 is 3 mol% The ZnO content is 2 mol% The CaO content is 1 mol% R2O is Na2O, and the content of Na2O is 39 mol%; The value of 0.85×SiO2+0.15×Al2O3+1.65×Y2O3 is 47.2; R2O is Na2O, and the value of 0.50×Na2O is 19.
5.
17. The method for preparing the ion sieve according to any one of claims 1-16, characterized in that, The process includes the following steps: after mixing all the raw materials according to the formula, the mixture is melted at 1300-1650℃ to obtain a liquid material; then it is made into granules, flakes or porous forms.
18. The preparation method according to claim 17, characterized in that, A granular ion sieve is formed by water quenching, wherein the water quenching temperature is 10-80℃.
19. A purification method using a salt bath for chemical strengthening of glass, characterized in that, The process includes the following steps: introducing the ion sieve according to any one of claims 1-16 into a salt bath to be purified at 350-550°C to carry out an impurity ion adsorption reaction.
20. The purification method according to claim 19, characterized in that, The amount of the ion sieve used is 0.5-5.0 wt% of the salt bath to be purified, and / or the adsorption reaction time is 0.1-48.0 h.
21. A method for preparing chemically strengthened glass, characterized in that, include: The glass to be strengthened and the ion sieve according to any one of claims 1-16 are introduced into a glass chemical strengthening salt bath free of impurity ions for chemical strengthening.
Citation Information
Patent Citations
Preparation method of chemically strengthened glass, chemically strengthened glass and raw material glass
CN112645609A
Boron-free phosphorus-free high-stability ion sieve and application thereof
CN112645610A